Strategies for motivational development in e-learning in a higher technology career - Herrera Martínez, Silvania Gabriela; Vásquez Villacis, María Irene; Fonseca Pinos, Lady Yadira; Mendoza Moyón, Cesar Israel (Revista Minerva, 2022)
The present study focuses on motivation, which is an essential element for the progress of learning and is inherent to the possibility of giving meaning and meaning to knowledge. Given that without motivation the student will not carry out an adequate activity, not only aligned to learn a concept, but also to implement didactic strategies that allow him to solve problems; Faced with the pandemic caused by the Covid-19 disease, teaching is maintained through virtual learning environments, which is a trend in many higher education institutions, which have been put into practice in development policies and academic prospects. The objective of the research was to investigate the importance of the motivation of students in the Assembly and Maintenance of computer equipment and virtual education. It was aligned in the type of documentary research of descriptive level and quantitative approach; a survey of students was used as a research instrument. Which evidenced results that determined that the motivation and use of didactic strategies by the teacher are essential in the teaching process before the virtual modality in students, since students in virtual learning environments must have characteristics that will help them to be responsible and Analytical.
Keywords: Motivation; Didactic strategies; Methods; Teachers